OPTIMALISASI PHOTOBOOTH SEBAGAI SARANA PROMOSI KESEHATAN DI KAMPUNG WISATA PONGGALAN-KARANGMIRI GIWANGAN UMBULHARJO YOGYAKARTA - Nugroho, Setyo Mahanani; Lestariningsih, Lestariningsih (Universitas Respati Yogyakarta, 2021)
Social media in this era is a new thing in the increasingly intensive means of communication in utilizing technological advancements. The health sector is also inevitable, so it must go along with this very rapid flow of change, especially in the health sector which deals with communication problems or the delivery of information to the public. Social media as a new media for health promotion is a belief. The approach method used for community service is community empowerment. Empowerment by building a photo booth as a means of health promotion by the community by utilizing consumables. Consumables that are used are goods collected from the Waste Bank in the Ponggalan-Karangmiri community. Photo booth with health messages that have been built titled